Research hotspots and frontiers of ethnic cultural identity——based on analysis of “web of science” database - Kuang, Lidan; Gao, Xingmei; Liu, Bingliang; Wang, Jianzhan (Frontiers in Psychology, 2023)
Cultural identity is of great significance to the formation of group consensus and the establishment of cultural self-confidence. In order to understand the history, current situation and trend, and provide theoretical support for future research, this paper makes a quantitative analysis of knowledge map including annual publication volume, trend, distribution of authors and institutions, co-occurrence, clustering and timeline of keywords as well as emergent keywords on the literature concerning ethnic cultural identity published in “Web of Science” database for a period from 2012 to 2022, with CiteSpace software as a tool. The results show an overall upward trend with diversified ethnic and regional characteristics; major institutions including universities of the U.S., the U.K., Australia, China and other countries and regions engage in their research from different disciplines such as psychology, sociology, ethnology and education; the researchers have not formed a core group of authors despite their accumulating number; research hotspots are indicated by keywords such as national identity, identity, ethnic identity and attitude; specifically, keyword clusters fall into three categories: emotional perception, multicultural identity process and ethnic cultural adaptability; researchers probe into various issues at different stages with direct relation to international situations and regional cultures. This study has positive implications for understanding and mastering the current research hotspots and development trends of ethnic cultural identity in the world.